Southern Ocean temperature records and ice-sheet models demonstrate rapid Antarctic ice sheet retreat under low atmospheric CO2 during Marine Isotope Stage 31 - Beltran, Catherine; Golledge, Nicholas R.; Ohneiser, Christian; Kowalewski, Douglas E.; Sicre, Marie-Alexandrine; Hageman, Kimberly J.; Smith, Robert; Wilson, Gary S.; Mainié, François (Quaternary science reviews, 2020)
Over the last 5 million years, the Earth’s climate has oscillated between warm (interglacial) and cold (glacial) states. Some particularly warm interglacial periods (i.e. ‘super-interglacials’) occurred under low atmospheric CO2 and may have featured extensive Antarctic ice sheet collapse. Here we focus on an extreme super-interglacial known as Marine Isotope Stage 31 (MIS31), between 1.085 and 1.055 million years ago and is the subject of intense discussion. We reconstructed the first Southern Ocean and Antarctic margin sea surface temperatures (SSTs) from organic biomarkers and used them to constrain numerical ice sheet-shelf simulations. Our SSTs indicate that the ocean was on average 5 °C (±1.2 °C) warmer in summer than today between 50 °S and the Antarctic ice margin. Our most conservative ice sheet simulation indicates a complete collapse of the West Antarctic Ice Sheet (WAIS) with additional deflation of the East Antarctic Ice Sheet. We suggest the WAIS retreated because of anomalously high Southern Hemisphere insolation coupled with the intrusion of Circumpolar Deep Water onto the continental shelf under poleward-intensified winds leading to a shorter sea ice season and ocean warming at the continental margin. In this scenario, the extreme warming we observed likely reflects the extensively modified oceanic and hydrologic system following ice sheet collapse. Our work highlights the sensitivity of the Antarctic ice sheets to minor oceanic perturbations that could also be at play for future changes. •Quantification of the Southern Ocean warming during MIS31 using molecular temperature reconstructions at high latitudes.•Sustained surface Southern Ocean warming & collapse of the sub-Antarctic ocean fronts under low atmospheric CO2 conditions.•Use of sea surface temperature data to test scenarios for the AIS retreat using coupled ice-sheet/ice-shelf model.•Two steps WAIS retreat: 1) mild ocean warming forcing ice margin retreat 2) rapid ocean warming as the ice sheet retreats.•We show that the Paris Agreement target temperature of 1.5°C is sufficient to drive runaway retreat of the WAIS.